Elevated contaminations and risks of novel organophosphate esters and their transformation products in paddy soils - Zixiao Zhao; Meng Gao; Mohan Ma; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; Hongwen Sun (Journal of Environmental Sciences, 2026)

Sea cucumber viscera-derived antifreeze peptides: identification, ice recrystallization inhibition activity, and ice-binding mechanism - Richeng Yu; Yang Zhao; Linnan Wang; Peng Ge; Zhupeng Zhang; Yuejuan Jia; Qianyun Ma; Wenxiu Wang; Jianfeng Sun (Food Research International, 2026)

A novel mycotoxin-degrading enzyme complex alleviates the combined toxicity of AFB1, DON, and ZEN in laying hens - Yan-Qi Ning; Yu Zhang; Yu-Hao Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun; Yu-Xuan Huang (Toxicon, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Interpretable and robust machine-learning prediction of CO2-H2O-coal wettability for deep CO2-enhanced coalbed methane and geological storage - Yunzhong Jia; Chenying Yu; Zhaolong Ge; Jiren Tang; Xiao Sun; Wenyu Fu (Gas Science and Engineering, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Ice breaking and water entry by a rigid sphere - Liang Sun; Zhangguo Ge; Yiheng Zhang; Ying Tang; Yiquan Yu; Zheyu Liu; Daoxin Zhou (Ocean Engineering, 2026)

Integrating emergy accounting with ecosystem-based coastal defence: An eco-coastal engineering framework for sustainability assessment of hybrid infrastructure - Junxue Zhang; Moran Yu; Hairuo Wang; Yan Gong; Haobing Wang; Xiaoting Zhai; Ashish T. Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men; Minghui Yang; et al. (Ocean Engineering, 2026)

Effects of fruit bagging on pesticide fate and fruit quality in peach under mixed-pesticide applications - Jun Yu; Pei Wang; Xiaolong Chen; Xing Sun; Jing Ge; Xiangyang Yu (Food Research International, 2026)

Hydrogeochemical and isotopic insights into source and human health risk of nitrate in groundwater from China's largest freshwater lake basin - Chunyi Wei; Shengpin Yu; Ximin Bai; Haiyan Liu; Zhen Wang; Olivier Pourret; Qin Ge; Hui Gui; Zhongkui Zhou; Zhanxue Sun (Groundwater for Sustainable Development, 2026)

Primer-programmed circular template generation enables padlock-free rolling circle amplification for low-background CRISPR-based pathogen detection - Yemin Han; Haotian Yu; Manman Lv; Mengqing Cheng; Weihao Li; Houyang Ge; Song Gao; Lu Yin; Qinyu Ge; Xinping Xu; Yan Huang; Longhua Sun; et al. (Analytica Chimica Acta, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

Structure and hepatoprotective activity of autophagy-related Butyriboletus roseoflavus polysaccharide - Zhen Sun; Huan Zhang; Dilida Yeerkenbieke; Lu Wang; Yongfeng Zhang; Chunyue Wang; Fan'ge Kong; Yu Li; Di Wang; Lanzhou Li (Carbohydrate Polymers, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Multiscale investigation of oxidative aging on thiol–functionalized montmorillonite: Correlating structural and chemical degradation to the reduced affinity for Hg(II) and MeHg - Ning Wang; Penggang Pei; Ge Gao; Yundi Kan; Linna Zhou; Bozhen Yu; Yuebing Sun (Journal of Environmental Chemical Engineering, 2026)

Deep learning-based realtime multiload response prediction and inverse analysis of offshore bridges - Zhu-Yu Sun; Yu-Tao Guo; Kang Ge; Chao Hou; Zhen-Zhong Hu (Engineering Structures, 2026)

Study on the migration mechanism of heavy metals in the supercritical water gasification of coal - Hao Sun; Jiayi Yu; Zhiwei Ge; Liejin Guo (Journal of Hazardous Materials, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Geochemical signatures, hydrocarbon generation kinetics, and oil-source correlation of the Es4 member source rocks in the Liaohe Western depression: implications for tight oil exploration in continental rift basins - Zhushi Ge; Xiaoping Liu; Xiaoguang Li; Yongcheng Chen; Chang Chen; Zilong Zhang; Biao Sun; Yi Zhong; Xueyou Tan; Gaohang Jia; Yu Xia; Zuowei Li; et al. (Fuel, 2026)

Underlying mechanism and the effect of diacylglycerols on the protein structural stability and in vitro digestibility of pork meatballs - Xinxin Zhao; Yunling Jiang; Zixin Luo; Xiankun Sun; Jiangyu Zhu; Hai Yu; Xinyan Peng; Qingfeng Ge (Food Chemistry, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Ultraviolet-treated riboflavin induces ROS-mediated apoptosis via inhibiting mitochondrial complex I in acute myeloid leukemia - Ruining Liu; Shuang Ge; Jinyuan Sun; Yi Liu; Liping Sun; Yang Yu; Deqing Wang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Ensemble Modelling Predicts Habitat Shifts for Portunus trituberculatus Under Climate Change in the East China Sea and the Yellow Sea of China - Fengqi Sun; Hongliang Zhang; Guoqiang Xu; Hui Ge; Lei Wu; Zhenhua Li; Shuwen Yu; Jiayi Zhou; Shihao Wang; Yongdong Zhou (Journal of Marine Science and Engineering, 2025)
This study systematically evaluated the dynamic habitat suitability of Portunus trituberculatus in the East China Sea and the Yellow Sea region (referred to herein as the East Yellow Sea region for brevity) under climate change impacts by integrating a species distribution model (Biomod2) with multi-source environmental data. Through the construction and evaluation of an ensemble model combining 10 algorithms, using the Area Under the Curve (AUC) and True Skill Statistic (TSS) for validation, we identified seabed temperature, seabed salinity, and chlorophyll as key environmental factors. Results showed that current high-suitability areas are concentrated in coastal Jiangsu, the Yangtze River estuary, and Zhoushan Archipelago waters, which overlap significantly with fishing hotspots. Under future climate scenarios, the species’ suitable habitat distribution is projected to shift significantly poleward: In the SSP5-8.5 scenario 2100, low/medium suitability areas increased by 38.2% and 88.2% respectively, while high-suitability areas decreased by 36.5%, with core spawning grounds (e.g., Zhoushan Archipelago waters) showing reduced suitability indices. The Bohai Sea’s summer water temperature unsuitability for Portunus trituberculatus migration creates an “ecological bottleneck” for northward expansion. The study proposes strengthening habitat management in Jiangsu coastal areas and integrating dynamic habitat prediction into fisheries policies to address climate-induced resource redistribution and ecosystem service changes. Our findings underscore the urgency of incorporating climate-driven habitat shifts into adaptive marine spatial planning and fisheries management frameworks.

Corrigendum to “Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms” [Science of the Total Environment, 880 (2023) 163314] - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Shuangxi Li; Peng Li (Science of The Total Environment, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Proteomic and flavor dynamics in irradiated scallop adductor muscle during refrigerated storage via 4D-DIA proteomics - Zhupeng Zhang; Peng Ge; Chaoqi Han; Jie Zhang; Richeng Yu; Wenxiu Wang; Ran Suo; Jianfeng Sun (Food Chemistry, 2025)

Synthetic phenolic antioxidants in paddy soils from central China: Contamination characteristics and risk prioritization analysis - Mohan Ma; Meng Gao; Zixiao Zhao; Siyuan Li; Yimeng Si; Liman Wei; Yiting Ge; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; et al. (Environmental Pollution, 2025)

Ensemble Experiments in an AI-NWP Coupled Framework: A Typhoon Case - Yangjinxi Ge; Donghai Wang; Zheng Yang; Junying Sun; Yu Jiang; Jiangli Zuo; Sunyi Yuan; Fengxian Wang (Journal of Meteorological Research, 2025)

A novel mycotoxin-degrading enzyme complex can biodegrade AFB1, DON, and ZEN co-contamination in both in vitro and in vivo experiments - Yan-Qi Ning; Zhe Peng; Yu Zhang; Alainaa Refaie; Jing-Hui Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun (Toxicon, 2025)

Selective interaction of BmNPV Bm65 with host proteins before and after ultraviolet radiation - Yutong Liu; Jiayin Huang; Guohui Li; Feifei Zhu; Qian Yu; Lindan Sun; Huiqing Chen; Liang Chen; Qi Ge; Shangshang Ma; Xiaoyong Liu; Keping Chen; et al. (Pesticide Biochemistry and Physiology, 2025)

Nanozeolite-coupled biochar-based phosphorus fertilizer decreases soil N2O emissions in a subtropical Moso bamboo forest - Xinyong Sun; Shuokang Liu; Caixian Tang; Jiashu Zhou; Zhenhui Jiang; Chang Dong; Yu Luo; Tida Ge; Jason C. White; Yanjiang Cai; Bing Yu; Yongfu Li (Journal of Environmental Management, 2025)

Flexural performance of concrete beams hybrid reinforced with bundled stainless steel bars and BFRP bars - Yi Zheng; Zeyang Sun; Shichao Song; Liuzhen Yao; Jin Chen; Yu Tang; Hanbin Ge (Engineering Structures, 2025)

Csde1 Mediates Neurogenesis via Post-transcriptional Regulation of the Cell Cycle - Xiangbin Jia; Wenqi Xie; Bing Du; Mei He; Jia Chen; Meilin Chen; Ge Zhang; Ke Wang; Wanjing Xu; Yuxin Liao; Senwei Tan; Yongqing Lyu; et al. (Neuroscience Bulletin, 2025)

Synergistic enhancement of Pt electrocatalyst stability and activity in hydrogen oxidation reaction by polyoxometalate and carbon dot co-boosting - Fei-Yang Yu; Zhong-Ling Lang; Xian Wang; Jing Sun; Yu-Chen Liu; Hua-Qiao Tan; Jun-Jie Ge; Yang-Guang Li; Zhen-Hui Kang (Science Bulletin, 2025)

Smartphone-assisted ultrasensitive colorimetric strategy based on Cu-CN single-atom nanozyme for acrylamide detection in fried food - Jia Ge; Xiaoyu Sun; Xinxin Li; Yu Yang; Lin Zhang; Lingbo Qu; Zhaohui Li (Food Chemistry, 2025)

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

A novel green plant protein from Lycium barbarum L. residue: Structure, physicochemical and functional properties - Haixuan Sun; Beiqi Wu; Weiben Ge; Yu Wang; Hongxin Wang (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Dietary intervention enhances fertility in obese male mice by regulating SLC2As - Liujia Sun; Xiaoqi Hong; Qi Zhu; Yu Xiang; Cen Xu; Lingling Weng; Jieyu Cai; Na Liang; Mingrui Xue; Hongshan Ge (Journal of Molecular Histology, 2025)

Synthetic phenolic antioxidant contamination in farmland soils induced by mulching films: Distribution and transformation pathways - Shanxing Wu; Meng Gao; Bo Fang; Lili Rong; Zhanpeng Ge; Hao Chen; Yiming Yao; Yu Wang; Hongwen Sun (Journal of Hazardous Materials, 2025)

Strategies optimization to improve environmental benefit of chicken manure anaerobic digestion in China: Insight from life cycle assessment - Fangzhou Wang; Shunan Zhao; Yizhu Sun; Ge Song; Yifan Sun; Kai Zhao; Ruiping Liu; Yu-You Li (Journal of Cleaner Production, 2025)

Stratified distribution of recycled components in the mantle of the South China Sea unveiled through magnesium isotopes - Zhen-Min Ge; Xiao-Long Huang; Fan Yang; Yang Yu; Guan-Hong Zhu; Le Zhang; Yu-Xin Cai; Guo-Hong Sun (Chemical Geology, 2025)

Urbanization has enhanced compound heatwaves - Peng Sun; Shifang Yu; Rui Yao; Zhongbao Sun; Vijay P. Singh; Yaojin Bian; Chenhao Ge; Qiang Zhang (Journal of Geographical Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Characterization of flavor profiles of water-boiled pork meatballs at different ultrasonic powers using solid-phase microextraction gas chromatography–mass spectrometry combined with electronic nose - Xinxin Zhao; Bangcheng Lai; Yunling Jiang; Xiankun Sun; Zixin Luo; Qingfeng Ge; Jiaxin Chen; Hai Yu (Meat Science, 2025)

Microglial membrane-coated nanoparticles for ACSL4-siRNA delivery in Parkinson’s disease - Heyue Lu; Bo Zhang; Min Ge; Juncheng Yu; Fei Ju; Jie Sun; You Lang Zhou; Lei Wang; Zhongzheng Jia (Chemical Engineering Journal, 2025)

TGF-β/SMAD Pathway Mediates Cadmium Poisoning-Induced Chicken Liver Fibrosis and Epithelial-Mesenchymal Transition - Jinyang Zhang; Yiming Sun; Miao Yu; Yihan Hu; Xiaodan Huang; Guijun Yang; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Corrigendum to “Cryopreservation of porcine skin-derived stem cells using melatonin or trehalose maintains their ability to self-renew and differentiate” [Cryobiology 107 (2022) 23–34] - Jia-Dong Sun; Yu Sun; Tian Qiao; Shu-Er Zhang; Paul W. Dyce; Yuan-Wei Geng; Ping Wang; Wei Ge; Wei Shen; Shun-Feng Cheng (Cryobiology, 2025)

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Corrigendum to ‘Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure’ [Environ. Pollut. 347 (2024) 123742] - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2025)

Engineering the microenvironment in Ba-doped Fe catalyst with alkali metal promoters for enhanced CO2 hydrogenation to α-olefins - Joshua Iseoluwa Orege; Yang Yu; Jian Wei; Qixin Fan; Jixin Zhang; Lifei Song; Qingjie Ge; Jian Sun (Chemical Engineering Journal, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Dissecting the cell microenvironment of ovarian endometrioma through single-cell RNA sequencing - Jiangpeng Wu; Siyu Xia; Wenting Ye; Yan Sun; Jing Cai; Fubing Yu; Haiping Wen; Xiuwei Yi; Taikang Li; Mingwei Chen; Jiayun Chen; Ge Song; et al. (Science China Life Sciences, 2025)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

Suitability evaluation of rural domestic sewage treatment processes in cold areas of Northeast China: Regional differences analysis and engineering application - Wenbin Zhao; Yuzhi Liu; Ge Yu; Shuang Zhong; Shuai Xia; Yang Sun; Donglei Zou (Journal of Environmental Management, 2024)

Provincial equity and enhanced health are key drivers for China's 2060 carbon neutrality - Jiaxin Dong; Siwei Li; Yisheng Sun; Weishu Gong; Ge Song; Yu Ding; Jie Yang; Mengfan Teng; Ruilin Wang; Jia Xing; Yang Ou; Wei Gong (Journal of Cleaner Production, 2024)

Crosslinking ability of hydrolyzed distarch phosphate and its stabilizing effect on rehydrated sea cucumber - Jiaqi Yu; Wenhao Ge; Kaifeng Wang; Wenhui Hao; Shangju Yang; Ying Xu; Tingyu Feng; Peng Han; Xun Sun (Food Chemistry, 2024)

Structure, physicochemical and adsorption properties of insoluble dietary fiber from Lycium barbarum residue: A potential functional factor - Haixuan Sun; Weiben Ge; Deao Song; Yubing Li; Yu Wang; Hongxin Wang (Food Bioscience, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Insighting the effect of lard-based diacylglycerol on the thermal gelation and rheological properties of myofibrillar protein influenced by soy protein isolate - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Mangang Wu; Qingfeng Ge; Xinyan Peng; Baohua Kong; Hai Yu (Food Hydrocolloids, 2024)

Multiscale experimental insights into vacuum drying of sludge for enhanced energy efficiency and emission control - Yang Yu; Xiaofeng Sun; Huarong Zhang; Weihong Wu; Tianxing Zhang; Shifu Ge (Science of The Total Environment, 2024)

Reactive oxygen species-responsive nanotherapy for the prevention and treatment of cerebral ischemia–reperfusion injury - Jianglong Kong; Runxuan Chu; Junjie Wen; Hongrui Yu; Jiawen Liu; Yuting Sun; Meiru Mao; Xiaohan Ge; Zixin Jin; Weimin Huang; Na Hu; Yi Zhang; et al. (Chemical Engineering Journal, 2024)

Membraneless organelles assembled by AuNPs-enzyme integration in non-photosynthetic bacteria: Achieving high specificity and selectivity for solar hydrogen production - Hui Li; Xiaoxuan Yu; Yaqi Wu; Cong Li; Zhengwei Xu; Wang Liu; Shuheng Chen; Hongcheng Sun; Yan Ge; Zhenhui Qi; Junqiu Liu (Chemical Engineering Journal, 2024)

For regenerated graphite: Tailoring sub-surface architecture with strong pre-storage abilities towards high-rate properties - Zhengqiao Yuan; Yu Dong; Zihao Zeng; Wenqing Zhao; Bin Wang; Hai Lei; Wei Sun; Xiaobo Ji; Yue Yang; Peng Ge (Chemical Engineering Journal, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Preparation, characterization, stability, and controlled release of chitosan-coated zein/shellac nanoparticles for the delivery of quercetin - Jiawen Liu; Hongrui Yu; Jianglong Kong; Xiaohan Ge; Yuting Sun; Meiru Mao; David Y. Wang; Yi Wang (Food Chemistry, 2024)

Spatial-temporal-controlled NO gas and PARP1 siRNA delivery for alleviating the dilemma of deeper sonodynamic therapy in pancreatic cancer - Qingshuang Tang; Yuan Wang; Ruiqi Wu; Zexing Yu; Xue Shi; Yang Song; Lulu Zhang; Xin Li; Jinxia Zhang; Suhui Sun; Xiaotu Ma; Shuyu Xu; et al. (Chemical Engineering Journal, 2024)

Overexpression of the Panax ginseng CyP gene enhances abiotic and biotic stress tolerance in transgenic Arabidopsis - Tianxia Sun; Miao Zhang; Huafeng Geng; Yuming Wang; Zhimei Liu; Dongming Xue; Wei Liu; Hongling Li; Shuaijun Li; Ge Hui; Yu Zhao (Physiological and Molecular Plant Pathology, 2024)

Are longer and more intense heatwaves more prone to extreme precipitation? - Peng Sun; Yaojin Bian; Shifang Yu; Rui Yao; Zhongtian Wang; Qiang Zhang; Wenhui Chen; Chenhao Ge; Zice Ma; Wenying Du (Global and Planetary Change, 2024)

Combined neurotoxicity of aged microplastics and thiamethoxam in the early developmental stages of zebrafish (Danio rerio) - Yanan Sun; Ping Ding; Jiayi Zhang; Kexin Sun; Xintong Li; Qing Ge; Yao Dang; Yunjiang Yu; Guocheng Hu (Environmental Pollution, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Pilot–scale vertical continuous–flow reactors applied to treat rural domestic wastewater at low temperature via aerobic granular sludge - Shibo Cong; Ge Yu; Shuai Xia; Haiyang Yu; Yang Sun; Yu Gao; Yuzhi Liu; Donglei Zou (Journal of Water Process Engineering, 2024)

Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2024)

Development of a nonstationary Standardized Precipitation Evapotranspiration Index (NSPEI) and its application across China - Peng Sun; Chenhao Ge; Rui Yao; Yaojin Bian; Huilin Yang; Qiang Zhang; Chong-Yu Xu; Vijay P. Singh (Atmospheric Research, 2024)

Unveiling a novel mechanism for competitive advantage of ciprofloxacin-resistant bacteria in the environment through bacterial membrane vesicles - Zuye Fang; Xinlu Zhao; Ziyuan Zhang; Jiayi Wu; Jiliang Cheng; Dan Lei; Nan Li; Ruiguang Ge; Qing-Yu He; Xuesong Sun (Journal of Hazardous Materials, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Natural and anthropogenic dissolved organic matter in landfill leachate: Composition, transformation, and their coexistence characteristics - Jing Zheng; Xian-Ge Wang; Yue Sun; Yu-Xin Wang; Hao-Qun Sha; Xiao-Song He; Xiao-Jie Sun (Journal of Hazardous Materials, 2024)

The promoting effect of electron beam irradiation on enzymatic saccharification and alcohol fermentation of sorghum meal: Related mechanisms - Mengting Yan; Chenyang Sun; Jiangtao Yu; Junqing Bai; Huishan Shen; Xiuyun Zhang; Yifan Lu; Zhuangzhuang Sun; Xiangzhen Ge; Wei Liang; Jie Zeng; Haiyan Gao; et al. (Journal of Cereal Science, 2024)

Identification of organic pollutants and heavy metals in natural rubber wastewater and evaluation its phytotoxicity and cytogenotoxicity - Dayu Zhu; Chengjun Ge; Ying Sun; Huamei Yu; Jun Wang; Hongfei Sun (Chemosphere, 2024)

Flow-through electrode system (FES): An effective approach for biofouling control of reverse osmosis membranes for municipal wastewater reclamation - Hao-Bin Wang; Yin-Hu Wu; Yi-Ge Sun; Yu-Qing Xu; Zhuo Chen; Song Xue; Zhuo-Wei Zhang; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2024)

Effects of ultrasound-assisted cooking on the physicochemical properties and microstructure of pork meatballs - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Meat Science, 2024)

Mxene-based wearable self-powered and photothermal triboelectric nanogenerator patches for wound healing acceleration and tactile sensing - Meiru Mao; Jianglong Kong; Xiaohan Ge; Yuting Sun; Hongrui Yu; Jiawen Liu; Weimin Huang; David Y. Wang; Yi Wang (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Development of alantolactone-loaded zein and shellac nanoparticles for controlled release in simulated gastrointestinal digestion - Hongrui Yu; Xiaohan Ge; Jianglong Kong; Yuting Sun; Meiru Mao; Jiawen Liu; Jiaxing Ye; Amit Arora; Inthawoot Suppavorasatit; Yi Wang (Journal of Food Engineering, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Comparative transcriptome analysis of eyes reveals the adaptive mechanism of mantis shrimp (oratosquilla oratoria) induced by a dark environment - Xiaoli Sun; Ling He; Bujin Ayi; Yuyang Qiu; Jiayue Xu; Wei Yu; Tinghao Yan; Ge Ding; Boping Tang; Gang Wang; Daizhen Zhang (Genetica, 2023)

Spatial distribution and risk assessment of polycyclic aromatic hydrocarbons in soils from contaminated sites in Eastern China - Xinhui Sun; Qi Zhao; Xuelin Li; Qiuyue Zhang; Meng Gao; Zhanpeng Ge; Yu Wang; Hongwen Sun (Environmental Geochemistry and Health, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

An approach for multi-objective optimization based on preliminary PSA and its applications for fusion reactors - Ming Sun; Jie Yu; Taosheng Li; Daochuan Ge (Annals of Nuclear Energy, 2023)

Identifying driving hydrogeomorphic factors of coastal wetland downgrading using random forest classification models - Keqi He; Wenhong Li; Yu Zhang; Ge Sun; Steve G. McNulty; Neal E. Flanagan; Curtis J. Richardson (Science of The Total Environment, 2023)

Design and analysis of wire-driven tail fin for bionic underwater glider - Liming Ge; Wenda Ma; Shaoqiong Yang; Xiao Yu; Tongshuai Sun; Xuan Wang; Shuai Fa; Yanhui Wang (Ocean Engineering, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

A dual receptor targeting and blood–brain barrier penetrating co-drug-loaded particle mediating inhibition of oxidative phosphorylation for targeted therapy of glioblastoma - Yuting Sun; Jianglong Kong; Xiaohan Ge; Meiru Mao; Hongrui Yu; Jiawen Liu; Yi Wang (Chemical Engineering Journal, 2023)

Aminotransferase Class I and II Gene Family in the Jinjiang Oyster (Crassostrea ariakensis): Genomewide Identification, Phylogenetic Analysis and Expression Profiles after Salinity Stress - Guangyu Ge; Zhihong Liu; Tao Yu; Liqing Zhou; Xiujun Sun; Zhuanzhuan Li; Yanxin Zheng (Fishes, 2023)
Aminotransferases are enzymes found in living organisms that catalyze transfer reactions between amino acids and keto acids, crucial for amino acid metabolism and synthesis. Aminotransferase classes I and II play a vital role in regulating osmolarity, protecting cells, and improving metabolic homeostasis and cellular fitness. To investigate the characteristics of the aminotransferase class I and II gene family and their roles in osmotic pressure regulation in the Jinjiang oyster (Crassostrea ariakensis), the gene structure, chromosomal localization, and phylogeny were characterized and the genes’ expression in the gill under high-salt stress was analyzed. In this study, eighteen Aminotransferase class I and II genes, including SPTLCa and SPTLCb, SPTa and SPTb, ALAT2a and ALAT2b, KAT3a and KAT3b, and ASTa, ASTb and ASTc, were identified. The physicochemical properties of 11 family members were stable, with their instability factors less than 40. Subcellular localization prediction showed that aminotransferase classes I and II were localized in the cytoplasm or mitochondria. Chromosomal localization results showed that the 18 aminotransferase class I and II genes were located on eight chromosomes. All members of this gene family had the Aminotran_1_2 structural domain which is associated with osmotic pressure regulation by adjusting the conversion reaction between amino acids and keto acids. Most gene expressions showed an initial increase followed by a decrease from 0 h to 12 h when the oysters were challenged by acute stress using artificial seawater with a salinity of 40. However, the expression of CarAGT2 and CarKAT3b genes showed an increased trend with increasing stress time. This study systematically investigated the bioinformatics characteristics of the aminotransferase class I and II gene family in C. ariakensis and their role in osmotic pressure regulation, which provides scientific data for understanding the potential functions of these genes in physiological adaptation, thereby expanding the research on osmoregulation in bivalves.

Modeling and optimization of synergistic ozone-ultraviolet-chlorine process for reclaimed water disinfection: From laboratory tests to software simulation - Ke-Fan Cao; Zhuo Chen; Yi-Ge Sun; Bang-Hao Huang; Qi Shi; Yu Mao; Yin-Hu Wu; Yun Lu; Hong-Ying Hu (Water Research, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Assessment of Joint Toxicity of Arsenate and Lead by Multiple Endpoints in Chlamydomonas reinhardtii - Danqing Sun; Zhongquan Jiang; Hangqi Yu; Zhen Li; Chunhua Zhang; Ying Ge (Bulletin of Environmental Contamination and Toxicology, 2023)

Multi-year nitrogen accumulation weakens the stabilizing effect of species asynchrony on drought resistance in a Tibetan alpine meadow - Ge Hou; Tiancai Zhou; Peili Shi; Jian Sun; Ning Zong; Jialuo Yu; Minghua Song (Agricultural and Forest Meteorology, 2023)

Liquid metal microspheres with an eddy-thermal effect for magnetic hyperthermia-enhanced cancer embolization-immunotherapy - Nailin Yang; Xingwei Sun; Yangkai Zhou; Xiaoyuan Yang; Jiaxi You; Zepeng Yu; Jun Ge; Fei Gong; Zhisheng Xiao; Yong Jin; Zhuang Liu; Liang Cheng (Science Bulletin, 2023)

Role of TPEN in Amyloid-β25–35-Induced Neuronal Damage Correlating with Recovery of Intracellular Zn2+ and Intracellular Ca2+ Overloading - Wen-bo Chen; Yu-xiang Wang; Hong-gang Wang; Di An; Dan Sun; Pan Li; Tao Zhang; Wan-ge Lu; Yan-qiang Liu (Molecular Neurobiology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Anti-ricin toxin human neutralizing antibodies and DMAbs protection against ricin toxin poisoning - Haotian Yu; Meng Wu; Na Zhao; Mingxin Dong; Yan Wang; Kaikai Yu; Chengbiao Sun; Na Xu; Liangpeng Ge; Wensen Liu (Toxicology Letters, 2023)

Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Xiaoyun Zang; Xiaomei Cai; Shuangxi Li; Peng Li (Science of The Total Environment, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

Porous carbon nanofibers supported Zn@MnO sorbents with high dispersion and loading content for hot coal gas desulfurization - Yu Feng; Man Zhang; Yangjie Sun; Chunyan Cao; Jiancheng Wang; Mingzheng Ge; Weilong Cai; Jie Mi; Yuekun Lai (Chemical Engineering Journal, 2023)

Whole genome evaluation analysis and preliminary Assembly of Oratosquilla oratoria (Stomatopoda: Squillidae) - Xiaoli Sun; Gang Wang; Jie Yang; Wei Yu; Jiayue Xu; Boping Tang; Ge Ding; Daizhen Zhang (Molecular Biology Reports, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

Effects of various microwave intensities collaborated with different cold plasma duration time on structural, physicochemical, and digestive properties of lotus root starch - Xiangxiang Sun; Zhuangzhuang Sun; Ahmed S.M. Saleh; Yifan Lu; Xiuyun Zhang; Xiangzhen Ge; Huishan Shen; Xiuzhu Yu; Wenhao Li (Food Chemistry, 2023)

Multi-functional pH-sensitive active and intelligent packaging based on highly cross-linked zein for the monitoring of pork freshness - Jianglong Kong; Xiaohan Ge; Yuting Sun; Meiru Mao; Hongrui Yu; Runxuan Chu; Yi Wang (Food Chemistry, 2023)

UPLC-QTOF-MS coupled with machine learning to discriminate between NFC and FC orange juice - Ruixue Sun; Ranran Xing; Jiukai Zhang; Ning Yu; Yiqiang Ge; Weiwei Zhang; Ying Chen (Food Control, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Identification and localization of morphological feature-specific metabolites in Reynoutria multiflora roots - Meng-Ting Cai; Yu Zhou; Wen-Luan Ding; Yu-Hong Huang; Ying-Shan Ren; Zhi-You Yang; Lei Zhang; Fei Sun; Hai-Biao Guo; Liang-Yun Zhou; Zhi-Hong Gong; Xiu-Hong Piao; et al. (Phytochemistry, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Insights into the characteristics and mechanism of vacuum drying technology for municipal sludge processing - Qixiang Zhu; Xiaofeng Sun; Shifu Ge; Yang Yu (Chemosphere, 2023)

An offshore subsurface thermal structure inversion method by coupling ensemble learning and tide model for the South Yellow Sea - Fangjie Yu; Fengzhi Sun; Jianchao Li; Ge Chen (Frontiers in Marine Science, 2022)
The South Yellow Sea Cold Water Mass (SYSCWM), which occurs in the South Yellow Sea (SYS) during summer, significantly impacts the hydrological characteristics and marine ecosystems but lacks fine interior data. With satellite observations, significant achievements have been made in reconstructing high-resolution ocean subsurface thermohaline structure based on machine learning. However, the accuracy of offshore subsurface parameter estimation will be affected due to the macro-tidal environment and fewer in situ observations. In this paper, we coupled the TPXO tide model and Light Gradient Boosting Machine algorithm to develop an inversion model of offshore subsurface thermal structure for the SYS using sea surface data and in situ observations. After light modelling, the subsurface temperature structure in the SYS is retrieved from sea surface parameters with a spatial resolution of 0.25° at depths of 0-55 m. Observation-based dataset (ARMOR3D) and in situ observations are used for model evaluation. According to the validation of the mooring buoy observations, the overall coefficient of determination (R 2 ), which determines the percentage of variance in the dependent variable that can be explained by the independent variable, is more than 0.95. Furthermore, the R 2 is improved by 12% due to coupling tide model below the thermocline during the maturity stage of SYSCWM, which is helpful for a better reconstruction of SYSCWM. Comparing with the cruise data, the average R 2 of the proposed model is 0.927 which is slightly better than the accuracy of the observation-based ARMOR3D dataset. Since the R 2 exceeds 0.8 in the most area of 121°E~123.5°E, 33°N~36°N, the reconstruction is reliable in this area. The method provides a new explorable direction for reconstructing the ocean thermal structure in offshore areas.

Self-assembling Bioadhesive Inspired by the Fourth Repetitive Sequence of Balanus albicostatus Cement Protein 20 kDa (Balcp-20 k) - Li Jia; Yabiao Yu; Jinyang Zheng; Hao Zhou; Qiang Liu; Wei Wang; Xinxin Liu; Xiuming Zhang; Dongtao Ge; Wei Shi; Yanan Sun (Marine Biotechnology, 2022)

The Pseudogene BMEA_B0173 Deficiency in Brucella melitensis Contributes to M-epitope Formation and Potentiates Virulence in a Mice Infection Model - Ge Zhang; Hao Dong; Yu Feng; Hui Jiang; Tonglei Wu; Jiali Sun; Xin Wang; Minghe Liu; Xiaowei Peng; Yinghui Zhang; Xiaoqian Zhang; Liangquan Zhu; et al. (Current Microbiology, 2022)

Synergistic removal of organic pollutants from water by CTF/BiVO4 heterojunction photocatalysts - Yan Yu; Yanan Sun; Beixiao Ge; Jiawen Yan; Kaili Zhang; Hui Chen; Jinxing Hu; Juntao Tang; Shuang Song; Tao Zeng (Environmental Science and Pollution Research, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Conditions of Mainland China’s Island Ecosystems and Associated Influencing Factors: Integrated Assessment of 42 Typical Island Ecosystems - Zhiyuan Ma; Weiwei Yu; Wanting Zhang; Feiyang Ge; Bin Chen; Wenjia Hu; Dian Zhang; Jianji Liao; Hao Huang; Yuanmin Sun; Haiping Huang (Frontiers in Marine Science, 2022)
Although China possesses a large number of islands, knowledge of their overall ecological condition is limited on a national scale. Accordingly, this study developed a comprehensive and quantitative island ecosystem assessment framework that incorporates environmental quality, biological structure, and landscape patterns. The framework was applied to 42 typical, representative islands within China’s coastal regions, including different climatic zones, area sizes, populations, and substratum lithologies. Results showed that the value range of the comprehensive index of island ecosystem condition ( CI island ) was significant (from 52.33 to 89.53, 71.72 average), and 85.4% of islands scored either “high” or “good,” indicative of their exceptional condition. However, conditions varied among different island components, indicating different challenges. Environmental quality index ( I env ) values ranged from 60.70 to 94.80 (79.72 average), where primary threats were seawater nutrient pollution, petroleum, and marine organism metal contamination. Biological structure index ( I bio ) values ranged from 43.50 to 89.40 (66.10 average), where primary threats were vegetation destruction and a reduction in marine biodiversity within intertidal and subtidal zones. Landscape pattern index ( I land ) values varied significantly (from 6 to 100, 72.36 average), where a key characteristic of highly developed islands was low natural landscape (vegetation) coverage. Conditions also varied among island climate zones, lithologies, area sizes, and levels of human habitation. Additionally, island ecosystem conditions were influenced by both natural and anthropogenic factors as well as area size, population, and GDP. Although distance to the mainland significantly correlated to ( I bio ), and ( CI island ), these parameters did not significantly correlate to ( I env ), which might be explained by that environmental quality was generally conditional on large-scale environments. This assessment is intended to provide a holistic perspective on island conditions in China while identifying key challenges and associated driving factors, which will greatly aid in establishing island-specific sustainable management practices.

Integrated 16S rRNA Gene Sequencing and LC-MS Analysis Revealed the Interplay Between Gut Microbiota and Plasma Metabolites in Rats With Ischemic Stroke - Wanfeng Wu; Yihang Sun; Ning Luo; Cheng Cheng; Chengting Jiang; Qingping Yu; Shaowu Cheng; Jinwen Ge (Journal of Molecular Neuroscience, 2021)

The comprehensive measurement method of energy conservation and emission reduction in the whole process of urban sewage treatment based on carbon emission - Yue Zhang; Tonggang Ge; Jing Liu; Yongli Sun; Yu Liu; Qing Zhao; Tengfei Tian (Environmental Science and Pollution Research, 2021)

A siphon drainage method for stabilizing bank slopes under water drawdown condition - Yang Yu; Chengcheng Lv; Dongfei Wang; Qi Ge; Hongyue Sun; Yuequan Shang (Natural Hazards, 2021)

A new self-starting drainage method for slope stabilization and its application - Hong-yue Sun; Qi Ge; Yang Yu; Fei-xiang Shuai; Cheng-cheng Lü (Bulletin of Engineering Geology and the Environment, 2021)

Protectin DX ameliorates inflammation in sepsis-induced acute lung injury through mediating PPARγ/NF-κB pathway - Haifa Xia; Yangyang Ge; Fuquan Wang; Yu Ming; Zhouyang Wu; Jingxu Wang; Shujun Sun; Shiqian Huang; Ming Chen; Weimin Xiao; Shanglong Yao (Immunologic Research, 2020)

A Novel Eyes Topical Drug Delivery System: CsA-LNC for the Treatment of DED - Anan Zhang; Rong Sun; Meixin Ran; Yaxin Deng; Ying Ge; Yunjing Zhu; Xiumei Tao; Lixia Shang; Jingxin Gou; Haibing He; Tian Yin; Yanjiao Wang; et al. (Pharmaceutical Research, 2020)

Comparative Metabolomic and Transcriptome Analysis Reveal Distinct Flavonoid Biosynthesis Regulation Between Petals of White and Purple Phalaenopsis amabilis - Xiaoqing Meng; Ge Li; Lingya Gu; Yu Sun; Zongyun Li; Jingran Liu; Xiaoqing Wu; Tingting Dong; Mingku Zhu (Journal of Plant Growth Regulation, 2020)

ACT001 modulates the NF-κB/MnSOD/ROS axis by targeting IKKβ to inhibit glioblastoma cell growth - Qiuying Li; Yu Sun; Bowen Liu; Jiabo Li; Xin Hao; Weizhi Ge; Xuemei Zhang; Shiqi Bao; Jianmiao Gong; Zhenhuan Jiang; Chuanjiang Qiu; Liqing Zhao; et al. (Journal of Molecular Medicine, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Chemical constituents from Alisma plantago - aquatica subsp . orientale (Sam.) Sam and their anti-inflammatory and antioxidant activities - Xin-Yu Zhao; Gang Wang; Yan Wang; Xiang-Ge Tian; Jian-Chao Zhao; Xiao-Kui Huo; Cheng-Peng Sun; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Xun Wang (Natural Product Research, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Two new protostane-type triterpenoids from Alisma orientalis - Xiu-Lan Xin; Xin-Yu Zhao; Xiao-Kui Huo; Xiang-Ge Tian; Cheng-Peng Sun; Hou-Li Zhang; Yan Tian; Yong Liu; Xun Wang (Natural Product Research, 2018)

Comparison of white spot syndrome virus infection resistance between Exopalaemon carinicauda and Litopenaeus vannamei under different salinity stresses - Qianqian Ge; Ge Yu; Ming Sun; Jitao Li; Jian Li (Journal of Ocean University of China, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A two‐domain protein triggers heat shock pathway and necrosis pathway both in model plant and nematode - Lifang Ruan; Huihui Wang; Ge Cai; Donghai Peng; Hua Zhou; Jinshui Zheng; Lei Zhu; Xixi Wang; Haoquan Yu; Seng Li; Ce Geng; Ming Sun (Environmental Microbiology, 2015)
Summary The entomopathogen B acillus thuringiensis is equipped with multiple virulent factors. The genome sequence of B . thuringiensis YBT 1520 revealed the presence of a two‐domain protein named Nel which is composed of a necrosis‐inducing phytophthora protein 1‐like domain found in phytopathogens and a ricin B ‐like lectin domain. The merging of two distantly related domains is relatively rare. Nel induced necrosis and pathogen‐triggered immunity ( PTI ) on model plants. The Nel also exhibited inhibition activity to nematode. Microscopic observation showed that the toxicity of Nel to nematodes targets the intestine. Quantitative proteomics revealed that Nel stimulated the host defence. The Nel thus possesses dual roles, as both toxin and elicitor. Remarkably, the Nel protein triggered a similar response, induction of the heat shock pathway and the necrosis pathway, in both model plants and nematodes. The unusual ability of Nel to function across kingdom suggests a highly conserved mechanism in eukaryotes that predates the divergence of plants and animal. It is also speculated that the two‐domain protein is the result of horizontal gene transfer ( HGT) between phytopathogens and entomopathogens. Our results provide an example that HGT occurs between members of different species or even genera with lower frequency are particularly important for evolution of new bacterial pathogen lineages with new virulence. B acillus thuringiensis occupies the same ecological niches, plant and soil, as phytopathogens, providing the opportunity for gene exchange.

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

A DEAD-box RNA helicase produces two forms of transcript that differentially respond to cold stress in a cryophyte (Chorispora bungeana) - Yu Yang; Zhenglong Sun; Chenchen Ding; Linna Ge; Likun Sun; Muqun Bai; Yuan Song; Shuyan Chen; Lizhe An (Planta, 2014)

A tripeptide (NSK) inhibits Japanese encephalitis virus infection in vitro and in vivo - Chen Li; Ling-ling Ge; Ya-ling Yu; Li Huang; Yue Wang; Ming-xia Sun; Hassan Ishag; Liang-xiao Ma; Xue-hua Li; Zhi-qiang Shen; Xiang Mao (Archives of Virology, 2014)

Elevation‐induced climate change as a dominant factor causing the late Miocene C 4 plant expansion in the Himalayan foreland - Haibin Wu; Zhengtang Guo; Joël Guiot; Christine Hatté; Changhui Peng; Yanyan Yu; Junyi Ge; Qin Li; Aizhi Sun; Deai Zhao (Global Change Biology, 2014)
During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

Rapid development of 36 polymorphic microsatellite markers for Tetranychus truncatus by transferring from Tetranychus urticae - Cheng Ge; Jing-Tao Sun; Yu-Nan Cui; Xiao-Yue Hong (Experimental and Applied Acarology, 2013)

Dynamic expression profiles of MMPs/TIMPs and collagen deposition in mechanically unloaded rat heart: implications for left ventricular assist device support-induced cardiac alterations - Lu Wang; Yu-Xian Xu; Xiao-Jie Du; Quan-Ge Sun; Ying-Jun Tian (Journal of Physiology and Biochemistry, 2013)

Dynamic analysis for gene expression profiles of endothelial colony forming cells under hypoxia - De-Cai Yu; Wen-Du Feng; Xian-Biao Shi; Zhi-Yong Wang; Wei Ge; Chun-Ping Jiang; Xi-Tai Sun; Yi-Tao Ding (Genes & Genomics, 2013)

Spectroscopic and Molecular Modeling Studies on the Interaction Between a Fluorine-Containing Triazole Derivative and Human Serum Albumin - Jia-Xin Fu; Yu-Shu Ge; Feng-Lei Jiang; Xiao-Hong Sun; Yang Liu; Yi Liu (Biological Trace Element Research, 2011)

Iron-containing lipoprotein SiaA in SiaABC, the primary heme transporter of Streptococcus pyogenes - Xuesong Sun; Ruiguang Ge; Dongmei Zhang; Hongzhe Sun; Qing-Yu He (JBIC Journal of Biological Inorganic Chemistry, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Transgenic Bacillus thuringiensis (Bt) cotton (Gossypium hirsutum) allomone response to cotton aphid, Aphis gossypii, in a closed-dynamics CO2 chamber (CDCC) - Gang Wu; Fa Jun Chen; Feng Ge; Yu-Cheng Sun (Journal of Plant Research, 2007)

A proteomic approach for the identification of bismuth-binding proteins in Helicobacter pylori - Ruiguang Ge; Xuesong Sun; Qing Gu; Rory M. Watt; Julian A. Tanner; Benjamin Chun Yu Wong; Harry Huaxiang Xia; Jian-Dong Huang; Qing-Yu He; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2007)

Morphological and behavioral consequences of recurrent seizures in neonatal rats are associated with glucocorticoid levels - Xiu-Yu Shi; Ji-Wen Wang; Ge-Fei Lei; Ruo-Peng Sun (Neuroscience Bulletin, 2007)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Pollen‐based biome reconstructions for China at 0 and 6000 years - Ge Yu; I. Colin Prentice; Sandy P. Harrison; Xiangjun Sun (Journal of Biogeography, 1998)
Biomization provides an objective and robust method of assigning pollen spectra to biomes so that pollen data can be mapped and compared directly with the output of biomgeographic models. We have tested the applicability of this procedure, originally developed for Europe, to assign modern surface samples from China to biomes. The procedure successfully delineated the major vegetation types of China. When the same procedure was applied to fossil pollen samples for 6000 years ago, the reconstructions showed systematic differences from present, consistent with previous interpretations of vegetation changes since the mid‐Holocene. In eastern China, the forest zones were systematically shifted northwards, such that cool mixed forests displaced taiga in northeastern China, while broad‐leaved evergreen forest extended c . 300 km and temperate deciduous forest c . 500–600 km beyond their present northern limits. In northwestern China, the area of desert and steppe vegetation was reduced compared to present. On the Tibetan Plateau, forest vegetation extended to higher elevations than today and the area of tundra was reduced. These shifts in biome distributions imply significant changes in climate since 6000 years ago that can be interpreted qualitatively as a response to orbital forcing and its secondary effects on the Asian monsoon.